Bede the Venerable in Polish Religious Prose of the 16th –18th Centuries - Puchalska-Dąbrowska, Bernadetta Maria (Tematy i Konteksty, 2021)
The aim of the article is to introduce Bede the Venerable as a role model present in Polish religious prose of the 16th–18th centuries. The sources under discussion are mainly collections of the lives of saints. The profile of Bede, shown as a perfect Benedictine monk, scholar and priest, is inspired by the earliest biographical Anglo-Saxon sources (e.g. Bede’s autobiography and Cuthbert’s letter concerning his death). Polish hagiography, following the directions of the Trent Council, aims at emphasising Bede’s qualities required from the clergy at that time – in-depth spiritual life, thorough knowledge, respect towards authorities, and teaching skills.